Pengembangan Bahan Ajar Fisika SMA Topik Fluida Berorientasi Masalah Lahan Basah Melalui Pendekatan Contextual Teaching and Learning (CTL) - Mega Selvia; Muhammad Arifuddin; Andi Ichsan Mahardika (Universitas Lambung Mangkurat, 2017)
school physics teaching materials problem-oriented topics fluid wetlands through approach Contextual Teaching And Learning (CTL) has not been optimally used in SMA PGRI 4 Banjarmasin. This adversely affects the learning outcomes. Therefore research material development through an approach Contextual Teaching And Learning (CTL) which aims to develop teaching materials such as lesson plans, worksheets, THB, and material teaching approach Contextual Teaching And Learning (CTL). The specific objective of the research to result in: (1) the validity of teaching materials school physics problem-oriented topics fluid wetlands through Contextual Teaching And Learning approach; (2) the practicality of teaching materials school physics problem-oriented topics fluid wetlands through Contextual Teaching And Learning approach, and (3) the effectiveness of teaching materials-oriented high school physics topics fluid wetland problem through an approach Contextual Teaching And Learning. Development of research methods to the design of Dick and Carey. Data obtained through the instrument validation sheet materials, instruments keterlaksanaan RPP observation sheets, and test. The results showed that: (1) teaching materials declared invalid by the high category. (2) teaching materials developed otherwise practical with very good category. (3) teaching materials developed that was declared effective in the high category. Research concluded that high school physics teaching materials problem-oriented topics fluid wetlands through approach Contextual Teaching and Learning (CTL) is declared unfit for use.